Maxillary Midline Diastemas in West African Smiles - Sefaakor Ahiaku, BDS (Hons); Brian J. Millar, BDS, FDSRCS, PhD, FHEA (Elsevier, 2023)
The maxillary midline diastema (MMD) has experienced a renaissance in popular culture over the last 10 years. Current literature states that MMDs should be eliminated where possible or be reduced to 1 mm or less in width. This literature review explores the evidence for this in a West African population. A systematic search of the literature (Medline and Google Scholar) followed by a hand search was carried out to identify all papers evaluating perceptions of MMDs. In all, 209 papers were identified in the literature search, 8 of which met the inclusion criteria. The review revealed that midline diastemas are desirable in this specific population with a width of 2 to 4 mm deemed as attractive. As many as 95% of participants found the MMD beautiful, and as many as 95% would consider having one created artificially. The literature does not support the position that MMDs larger than 1 mm should always be treated to be perceived as attractive in this population. MMDs are accepted as attractive and should be considered a key feature in smile design for this population.